Governance and Cost Management in Marine Decarbonization: A Systematic Review: A Systematic Review - Alam, Arya Pamungkas Pitu; Aurelia, Dini; Nadhilah, Elva; Adelina, Alya Zalfa (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the pivotal role of managerial accounting in supporting governance, cost management, and risk integration within low-carbon marine projects under the blue economy transition. Despite escalating global commitments to marine decarbonization and biodiversity protection, existing literature remains fragmented and largely focused on macro-level policy and finance, leaving a critical void in internal managerial mechanisms. Using a Systematic Literature Review (SLR) approach based on the PRISMA protocol, this study synthesizes 33 relevant articles published between 2022 and 2026, capturing the transformative impact of the Kunming-Montreal Global Biodiversity Framework (KM-GBF) and the Taskforce on Nature-related Financial Disclosures (TNFD). The findings reveal three core systemic issues. First, biodiversity-related costs are economically material yet systematically excluded from formal costing systems due to the absence of standardized metrics. Second, biodiversity risk remains difficult to integrate into capital budgeting, often manifesting indirectly through financial pressures and operational disruptions. Third, managerial accounting plays a critical but underutilized governance role, bridging external sustainability demands with internal control systems, though often limited by symbolic implementation. This study contributes by proposing an integrated conceptual framework that positions cost management, biodiversity risk, and governance as interdependent dimensions of a single managerial accounting challenge, providing a strategic roadmap for aligning financial precision with ecological necessity in the blue transition.